Sosialisasi Pemanfaatan Air Hujan dengan Pembuatan Sumur Resapan Untuk Penanggulangi Banjir/Genangan dan Konservasi Air Tanah di SMP Negeri 8 Menteng Jakarta Pusat - Endah Lestari (Terang, 2019)
In recent years floods and droughts have occurred in various places in Indonesia. Java is one of the islands that often experiences flooding. During the rainy season floods cause several major cities to be submerged. Jakarta was hit several times by severe flooding. Flood events that occurred in 2007 caused approximately 60% of the DKI area to be submerged by a depth of more than 5 meters. PKM Partners is a public junior high school building located in Menteng, Central Jakarta. The Mitra area in the last few years has experienced a flood, it is quite disturbing the teaching and learning process in the Mitra area. The clean water crisis also occurs in the Mitra area, this is due to the location of the Mitra which is quite close to office buildings that have large enough water needs. The average rainfall in Indonesia is 2779 mm per year, in Jakarta around 2500 mm per year, with 180 days / year of rainy days. With a large enough rainfall average is the potential of water resources that can be utilized optimally. With the potential of existing water resources, it is necessary to have efforts to utilize water resources, especially rainwater, one of which is by making water infiltration techniques into the ground in the form of infiltration wells. Through this outreach activity, it is hoped that it can develop public awareness on how to tackle flooding on a small scale, namely at the household level to a wider level, schools, office buildings, etc. by using infiltration well technology in handling floods. and groundwater conservation.